(3GdhajGJs - (3GHf bfaP , CHh GdYHGS CMeO Hf GdMSjf Hf Ydj Hf GdNWjH Hf bfaP GdbSfWjfj, GHf GdNWjH, GHf bfaP,J (B810 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CPcQ ai gPG GdcJGH eG MVQfi ef hajGJ GdUMGHIhGdYdeGA hGdeMOKjf hGdeDdajf hQJHJg Ydi GdeHjf HhLg de CSHb Edjg s
(3BNQgG (B:s
(3ChdeG MceJ di Hg aNGWHg HPdc bHd Pdc cdg dCfg GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B117 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B205s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs